Chaotic diffeomorphism on manifold (smooth manifold) - Ali A. Shihab; Mizal H. Al-Obaidi; Jehan Hamad Hazaa (Tikrit Journal of Pure Science, 2019)
In this paper  we concern in studying chaotic homeomorphisms deals with study and investigate of chaotic homeomorphisms on smooth manifolds. For connections more precisely to chaotic diffeomorphisms maps on smooth manifolds.